The Effect of Herbal Probiotic Supplementation on the Growth Performance and Survival Rate of Nile Tilapia (Oreochromis niloticus) in a Closed Aquaculture System - Aini, Nila Robiatul; Diniarti, Nanda; Diamahesa, Wastu Ayu (Jurnal Biologi Tropis, 2025)
Nile tilapia (Oreochromis niloticus) is a high-value aquaculture commodity with steadily increasing market demand. However, the growth performance of Nile tilapia fingerlings is often hindered by suboptimal feed quality and high mortality rates. One innovative approach to address these challenges is the incorporation of herbal probiotics as feed additives. This study aimed to evaluate the effect of herbal probiotic supplementation (Probal) on the growth, feed efficiency, and survival of Nile tilapia fingerlings. The research was conducted over 28 days at the Laboratory of Fish Production and Reproduction, Faculty of Agriculture, University of Mataram, using a Completely Randomized Design (CRD) with four treatments and three replications: P1 (control), P2 (Probal 2.5%), P3 (Probal 3%), and P4 (Probal 3.5%). The observed parameters included absolute length and weight gain, specific growth rate (SGR), feed conversion ratio (FCR), feed utilization efficiency (EPP), feed consumption, survival rate (SR), and water quality. Results showed that P4 treatment significantly outperformed other treatments in terms of length gain (2.39 cm), weight gain (13.8 g), SGR (3.26%/day), and SR (93.33%). Although no significant differences were observed in FCR and FUE, Probal supplementation was proven to enhance growth performance and survival. Therefore, herbal probiotic supplementation represents a promising and environmentally friendly strategy for sustainably improving Nile tilapia aquaculture productivity.